The Effect of Childbirth Education in Reducing Anxiety in Facing Childbirth in the Third Trimester Pregnant Women: Scoping Review - Juliana Safitri Ritonga; Asri Hidayat (Poltekkes Kemenkes Palu, 2023)
Mothers unable to fight anxiety and fear, especially third-trimester pregnant women, will experience the release of catecholamine hormones in high concentrations and experience increased labour pain, obstructed labour, and discomfort during labour. The purpose is to analyze the effect of childbirth education in Reducing Anxiety in Facing Labor in Third Trimester Pregnant Women by including relevant sources of evidence from each article. The method in this study uses databases, namely Pubmed, ScienceDirect, and Wiley, published between 2012-2022. The results showed that of the nine articles reviewed, seven reports came from developing countries, namely Indonesia and Iran. Two words came from developed countries, namely Australia and that the existence of childbirth education would significantly reduce the level of maternal anxiety so that the delivery process could run smoothly and childbirth education will reduce the desire of pregnant women to give birth by SC. While previous research stated that the cause of anxiety in facing childbirth is, experience and stress can be influenced by family support, marital status, history of disease, mother's age and level of education.